ErbB2 (HER2)-CAR-NK-92 cells for enhanced immunotherapy of metastatic fusion-driven alveolar rhabdomyosarcoma - Heim, Catrin; Moser, Laura M.; Kreyenberg, Herman; Bonig, Halvard B.; Tonn, Torsten; Wels, Winfried S.; Gradhand, Elise; Ullrich, Evelyn; Meister, Michael T.; Koerkamp, Marian Groot; Holstege, Frank C. P.; Drost, Jarno; et al. (Frontiers in Immunology, 2023)
Introduction Metastatic rhabdomyosarcoma (RMS) is a challenging tumor entity that evades conventional treatments and endogenous antitumor immune responses, highlighting the need for novel therapeutic strategies. Applying chimeric antigen receptor (CAR) technology to natural killer (NK) cells may offer safe, effective, and affordable therapies that enhance cancer immune surveillance. Methods Here, we assess the efficacy of clinically usable CAR-engineered NK cell line NK-92/5.28.z against ErbB2-positive RMS in vitro and in a metastatic xenograft mouse model. Results Our results show that NK-92/5.28.z cells effectively kill RMS cells in vitro and significantly prolong survival and inhibit tumor progression in mice. The persistence of NK-92/5.28.z cells at tumor sites demonstrates efficient antitumor response, which could help overcome current obstacles in the treatment of solid tumors. Discussion These findings encourage further development of NK-92/5.28.z cells as off-the-shelf immunotherapy for the treatment of metastatic RMS.